Resilient therapy as an expansion of counseling services in working with the vulnerable clients - Madihie, Amalia (COUNS-EDU: The International Journal of Counseling and Education, 2016)
This conceptual paper introduces Resilient Therapy and resilience framework- The Magic Box. The resilience framework, The Magic Box Model was applied in developing Resilient Therapy Intervention (RT-I) in counseling services. The framework consists of five domains also known as potions: Basics, Belonging, Learning, Coping and Core Self Potions will be discussed in details. Resilient Therapy (RT) has been introduced as one of the strategic methodologies in working with children and families. RT discusses four key principles named The Noble Truths: Accepting, Conserving, Commitment and Enlisting. The therapy itself is a non-clinical approach and able to be applied by non-professional counselors such as guardians, volunteers, medical doctors, social officers, and even by parents. At the end of this paper, the summary of Resilient Therapy Intervention is explained in building resilience in vulnerable clients from the perspective of counseling